Analysis of the Effect of Indonesia's Per Capita Income on Household Electricity Consumption from 2018 to 2022 Using Correlation Coefficient and Simple Regression Methods - Nugroho, Verianto (Indonesian Journal of Electrical Engineering and Electronics, 2024)
Nowadays, electricity has become one of the essential factors in daily life. It can be said that almost every object around us uses electricity to function. The main factor influencing electricity usage is the number of electronic devices in a person's home, which is also affected by that individual's income. This study aims to analyse the effect of Indonesia's per capita income on household electricity consumption from 2014 to 2022. Simple linear correlation and regression methods are used to identify the relationship between the variables of per capita income and household electricity consumption. Economic and electricity consumption data were obtained from official sources, and the analysis was conducted using the latest statistical software.